The Role of Cancer-Associated Fibroblasts in Hepatocellular Carcinoma and the Value of Traditional Chinese Medicine Treatment - Jia, Wentao; Liang, Shufang; Cheng, Binbin; Ling, Changquan (Frontiers in Oncology, 2021)
Invasion and metastasis are the main reasons for the high mortality of liver cancer, which involve the interaction of tumor stromal cells and malignant cells. Tumor associated fibroblasts (CAFs) are one of the major constituents of tumor stromal cells affecting tumor growth, invasion, and metastasis. The heterogeneous property and source of CAFs make both tumor-supporting and tumor-suppression effects possible. The mechanism for CAFs in supporting HCC progression can be categorized into the upregulated aggressiveness and stemness, the transformed metabolism towards glycolysis and glutamine reductive carboxylation, the polarized tumor immunity towards immune escape of HCC cells, and the increased angiogenesis. The tumor suppressive effect of fibroblasts highlights the functional heterogenicity of CAFs populations and provides new insights into tumor-stromal interplay mechanisms. In this review, we introduced several key inflammatory signaling pathways in the transformation of CAFs from normal stromal cells, and the heterogeneous biofunction of activated CAFs. In view of the pleiotropic regulation property of traditional Chinese medicine (TCM) and heterogeneous effect of CAFs, we also introduced the application and values of TCM in the treatment of HCC through targeting CAFs.